Clinical and Microbiological Aspect of Wound Infection: A Review Update (Bangladesh Journal of Infectious Diseases, 2015)
Wound infection is frequently found. Infection of the wound happened due to entry of the bacteria through breached skin. These bacteria stop healing and produce sign and symptoms. From the beginning of the civilization scientist are fighting against infection. It is evident that wound infection is a challenging situation for the physicians. Multiple organisms can cause wound infection. For the treatment of infection a large number of antibiotics are used. Both broad spectrum and narrow spectrum antibiotics are available nowadays. It is ideal to give proper antibiotic after culture and sensitivity of the wound swab, pus or infected tissue. Improper and irrational use of antibiotics and genetic and non-genetic drug resistant mechanisms of bacteria lead to drug resistance. Wound infection can be recognized by various sign symptoms. The inflammatory response is a protective mechanism that aims to neutralize and destroy any toxic agents at the site of an injury and restore tissue homeostasis. The classic signs of infection include: localized erythema, pain, heat, cellulitis and oedema. Other criteria include: Abscess, discharge, delayed healing, discolouration of tissues within and at the wound margins, friable & bleeding granulation tissue. Unexpected pain or tenderness, abnormal smell, wound breakdown wound pocketing are also seen in wound infection.Bangladesh Journal of Infectious Diseases 2014;1(2):32-37